Diagnosing solar wind origins using in situ measurements in the inner heliosphere. Issue 2 (22nd October 2018) - Stansby, D; Horbury, T S; Matteini, L
ABSTRACT: Robustly identifying the solar sources of individual packets of solar wind measured in interplanetary space remains an open problem. We set out to see if this problem is easier to tackle using solar wind measurements closer to the Sun than 1 au, where the mixing and dynamical interaction of different solar wind streams is reduced. Using measurements from the Helios mission, we examined how the proton core temperature anisotropy and cross-helicity varied with distance. At 0.3 au there are two clearly separated anisotropic and isotropic populations of solar wind that are not distinguishable at 1 au. The anisotropic population is always Alfvénic and spans a wide range of speeds. In contrast the isotropic population has slow speeds, and contains a mix of Alfvénic wind with constant mass fluxes and non-Alfvénic wind with large and highly varying mass fluxes. We split the in situ measurements into three categories according these observations, and suggest that these categories correspond to wind that originated in the core of coronal holes, in or near active regions or the edges of coronal holes, and as small transients form streamers or pseudo-streamers. Although our method by itself is simplistic, it provides a new tool that can be used in combination with other methods for identifying the sources of solar wind measured by Parker Solar Probe and Solar Orbiter .